2015
DOI: 10.1016/j.mayocp.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Kidney Injury, Dialysis, and Mortality in Patients With Chronic Kidney Disease After Intravenous Contrast Material Exposure

Abstract: Objective To examine the effect of intravenous iodinated contrast material administration on the subsequent development of acute kidney injury (AKI), emergent dialysis, and short-term mortality using a propensity score-adjusted analysis of Computed Tomography (CT) scan recipients with chronic kidney disease (CKD). Patients and Methods In this IRB approved retrospective study, all CKD patients who received a contrast-enhanced (contrast group) or unenhanced (noncontrast group) CT scan from January 2000 to Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 21 publications
8
71
1
1
Order By: Relevance
“…Patients in this study who developed renal injury within 48 hours of intervention did not have an increased risk for hemodialysis or mortality. These findings parallel those reported by McDonald et al who reported intravenous contrast material was not associated with increased risk of hemodialysis and mortality among 6,902 subjects (42). …”
Section: Discussionsupporting
confidence: 91%
“…Patients in this study who developed renal injury within 48 hours of intervention did not have an increased risk for hemodialysis or mortality. These findings parallel those reported by McDonald et al who reported intravenous contrast material was not associated with increased risk of hemodialysis and mortality among 6,902 subjects (42). …”
Section: Discussionsupporting
confidence: 91%
“…These rates of AKI in this high-risk population are higher than the rates reported in the literature [3,7,8]. This is likely explained by 2 factors.…”
Section: Discussioncontrasting
confidence: 61%
“…Candidates for TAVR often have co-morbidities such as chronic renal failure that can adversely impact outcomes (20)(21)(22). There has been ongoing debate about the actual incidence, significance and even existence of acute kidney injury following intravenous iodinated contrast media injection during CT (23)(24)(25)(26)(27)). However, current guidelines recommend careful or limited use of iodinated contrast in patients with renal dysfunction (28), and reduction of contrast agent volume is desirable in patients with chronic renal failure.…”
Section: Low Dose Tavr Ctamentioning
confidence: 99%